An organ-wide spatiotemporal transcriptomic and cellular atlas of the regenerating zebrafish heart - Lei Li; Meina Lu; Lidong Guo; Xuejiao Zhang; Qun Liu; Meiling Zhang; Junying Gao; Mengyang Xu; Yijian Lu; Fang Zhang; Yao Li; Ruihua Zhang; et al. (Nature Communications)
Abstract Adult zebrafish robustly regenerate injured hearts through a complex orchestration of molecular and cellular activities. However, this remarkable process, which is largely non-existent in humans, remains incompletely understood. Here, we utilize integrated spatial transcriptomics (Stereo-seq) and single-cell RNA-sequencing (scRNA-seq) to generate a spatially-resolved molecular and cellular atlas of regenerating zebrafish heart across eight stages. We characterize the cascade of cardiomyocyte cell states responsible for producing regenerated myocardium and explore a potential role for tpm4a in cardiomyocyte re-differentiation. Moreover, we uncover the activation of ifrd1 and atp6ap2 genes as a unique feature of regenerative hearts. Lastly, we reconstruct a 4D “virtual regenerating heart” comprising 569,896 cells/spots derived from 36 scRNA-seq libraries and 224 Stereo-seq slices. Our comprehensive atlas serves as a valuable resource to the cardiovascular and regeneration scientific communities and their ongoing efforts to understand the molecular and cellular mechanisms underlying vertebrate heart regeneration.